Preparation, optimization, and characterization of simvastatin nanoparticles by electrospraying: An artificial neural networks study. Issue 28 (8th April 2016) - Imanparast, Fatemeh; Faramarzi, Mohammad Ali; Paknejad, Maliheh; Kobarfard, Farzad; Amani, Amir; Doosti, Mohmood
ABSTRACT: The purpose of this study was to determine major factors impacting the size of simvastatin (SIM)‐loaded poly(d, l ‐lactic‐ co ‐glycolide) (PLGA) nanoparticles (NPs) that was prepared using electrospraying. Three variables including concentration of polymer and salt as well as solvent flow rate were used as input variables. Size of NPs was considered as output variable. For the first time, our findings using a systematic and experimental approach, showed the importance of salt concentration as the dominant factor determining the size with a sharp and reverse effect. Optimum formulation (i.e., flow rate 0.08 mL h −1, polymer concentration 0.7 w/v %, and salt concentration 0.8 m M ) was then evaluated for aqueous solubility, encapsulation efficiency, particle size, in vitro drug release pattern and cytotoxicity. A very appreciable encapsulation efficiency (90.3%) as well as sustained release profile, considerable enhancement in aqueous solubility (∼5.8 fold) and high IC50 (>600 µ M of SIM‐loaded PLGA NPs) indicated PLGA as a promising nanocarrier for SIM. The optimum formulation had particle size, zeta potential value, polydispersity index (PDI) and drug loading of 166 nm, +3 mV, 0.62 and 9%, respectively. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43602. Abstract :